An economically based evaluation index for perennial and short‐term ryegrasses in New Zealand dairy farm systems. (11th January 2016) - Chapman, D. F.; Bryant, J. R.; Olayemi, M. E.; Edwards, G. R.; Thorrold, B. S.; McMillan, W. H.; Kerr, G. A.; Judson, G.; Cookson, T.; Moorhead, A.; Norriss, M.
Abstract: Grazed pastures based on ryegrass species provide most of the feed for dairy cattle in New Zealand. There are many cultivars of perennial ( Lolium perenne ), annual and Italian ( L. multiflorum ), and hybrid ( L. boucheanum ) ryegrasses available for dairy farmers to use in pasture renewal. This study describes an index which ranks ryegrass cultivars relative to a genetic base according to the estimated economic value (EV) of seasonal dry matter (DM) traits. A farm system model was used to derive EVs ($ ha −1 calculated as change in operating profit divided by unit change of the trait) for additional DM produced in different seasons of the year in four regions. The EV of early spring DM was consistently high across all regions, whereas EV for late spring DM was moderate to low. Genotype × environment analysis revealed significant reranking of DM yield among ryegrass cultivars across regions. Hence, separate performance values (PVs) were calculated for two mega‐environments and then combined with the corresponding season and region EV to calculate the overall EV for twenty‐three perennial ryegrass and fifteen short‐term ryegrass cultivars. The difference in operating profit between the highest ranked and lowest ranked perennial ryegrass cultivar ranged from $556 ha −1 to $863 ha −1  year −1 depending on region. For short‐term ryegrasses used for winter feed, the corresponding range was $394 to $478 ha −1  year −1 . Using PV for DM yield, it was estimated that plant improvement in perennial ryegrass has added $12–$18 ha −1  year −1 (depending on region) operating profit on dairy farms since the mid‐1960s.